The Impact of Financial Ratios on Stock Returns with Labor Education Costs as Moderator in IDX Banks - Salwaa Ardhiah Mohamad; Muhammad Amir Arham; Frahmawati Bumulo; Syarwani Canon; NIswatin, NIswatin; Meyko Panigoro (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the effect of financial performance ratios on stock returns by considering the role of labor education costs as a moderating variable in conventional banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2009-2023. The financial performance ratios studied include Net Interest Margin (NIM), and Loan Deposit Ratio (LDR). The study used a quantitative approach with a moderated regression analysis method on panel data. The findings show that financial performance ratios significantly affect stock returns. In addition, labor education costs proved to be able to moderate the relationship between financial performance ratios and stock returns, indicating the importance of investing in human resource development to improve financial performance and investment attractiveness. This study provides theoretical implications on the development of microeconomic theory and practical recommendations for the management of banking companies and regulators that the cost of labor education is not only recognized as a company expense in the short term. However, the cost of labor education is able to increase operational efficiency which affects the profitability and securities of banking companies in the long term and is considered to be a strategic step for companies in facing future challenges.